2022
DOI: 10.1155/2022/7625739
|View full text |Cite|
|
Sign up to set email alerts
|

AXL Inhibits Proinflammatory Factors to Relieve Rheumatoid Arthritis Pain by Regulating the TLR4/NF-κB Signaling Pathway

Abstract: Objective. This study aims to explore the role and mechanism of AXL receptor tyrosine kinase (AXL) in relieving inflammatory pain caused by rheumatoid arthritis (RA). Methods. RA mouse model was constructed by collagen antibody induction. RT-qPCR and Western blot were used to detect the level of AXL in RA fibroblast-like synovial cells (RA-FLS) and joint synovium. The levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and nitric oxide (NO) were detected by ELISA. The inflammatory infiltration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Slices, 6 μm thick, were prepared at a 5° angle to the paraffin surface, followed by 5‐min each soak in 100%, 95%, 85%, and 75% graded ethanol, and 5‐min staining with hematoxylin and 2‐min eosin staining to assess joint pathology. Joint pathology was assessed by inflammation degree, conducted by three experts on a scale from 0 to 4: 0, no inflammation; 1 to 2, mild inflammation; 3, moderate inflammation; and 4, severe inflammation 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slices, 6 μm thick, were prepared at a 5° angle to the paraffin surface, followed by 5‐min each soak in 100%, 95%, 85%, and 75% graded ethanol, and 5‐min staining with hematoxylin and 2‐min eosin staining to assess joint pathology. Joint pathology was assessed by inflammation degree, conducted by three experts on a scale from 0 to 4: 0, no inflammation; 1 to 2, mild inflammation; 3, moderate inflammation; and 4, severe inflammation 14 …”
Section: Methodsmentioning
confidence: 99%
“…Joint pathology was assessed by inflammation degree, conducted by three experts on a scale from 0 to 4: 0, no inflammation; 1 to 2, mild inflammation; 3, moderate inflammation; and 4, severe inflammation. 14 2.6 | Tartrate-resistant acid phosphatase (TRAP) staining…”
Section: Hematoxylin and Eosin (He) Staining And Inflammation Scoringmentioning
confidence: 99%
“…These data implicate MERTK as a critical efferocytosis receptor in mouse models of RA. Role of AXL in efferocytosis in arthritic joints is less clear, though evidence of its protective role is also shown in the CAIA model by reduced inflammation of the joints injected with lentiviral Axl expression vectors 49 . TYRO3, on the other hand, contributes to synovial hyperplasia and osteoclast activation in K/BxN serum‐induced arthritis, as Tyro3 −/− mice display reduced joint inflammation and bone erosion 50 .…”
Section: Phosphatidylserine Recognition In Ramentioning
confidence: 99%
“…Role of AXL in efferocytosis in arthritic joints is less clear, though evidence of its protective role is also shown in the CAIA model by reduced inflammation of the joints injected with lentiviral Axl expression vectors. 49 TYRO3, on the other hand, contributes to synovial hyperplasia and osteoclast activation in K/BxN serum-induced arthritis, as Tyro3 −/− mice display reduced joint inflammation and bone erosion. 50 Collectively, these studies suggest non-overlapping functions of different PtdSer receptors in inflammatory arthritis.…”
Section: Phos P Hat Idy L S E Rine Recog Nition In R Amentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%